Cosmomedia: Natural Dyes in Japan - Ganaele Langlois (Media Theory)
This article explores John Durham Peters’ concepts of ‘communication as (impossible) communion’ and ‘elemental media’ by turning to the Japanese traditions of naturally dyed textiles. The article explores the politics of encounter that naturally-dyed textiles enable and links them to the question of world-making. It further examines how the extraction and application of color from the environment engages not only with humans and culture, but with non-human agencies and environmental politics as well. It links John Durham Peters’ work with that of Yuk Hui, particularly through elaborating on cosmotechnics as the ethics of technics, understood here as transformative modes of relations to the world, to non-humans and to more-than-humans.